Enhancing the Quality of Local Government Public Services Through an Integrated Online Licensing Application - Betty Krisdayanti Sihombing; Timbul Dompak; Lubna Salsabila; Etika Khairina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The objective of this study is to examine how the implementation of E-Government, specifically through the PTSP application in Batam City, enhances the quality of public services. The development of E-Government policies represents a significant advancement in information and communication technology within the context of globalization. In today's modern society, this development is inseparable from the increasing demands placed on governments as service providers to be more effective, efficient, and transparent in their administrative duties. Consequently, the concept of good governance has emerged, emphasizing the need for governments to meet these demands. The research design employed in this study involves a literature review using a qualitative approach. The focus is on analyzing and describing the implementation of E-Government in public services through the PTSP application at the Batam City One-Stop Investment and Licensing Service Office. Primary and secondary data sources are utilized, and data collection techniques include observation, interviews, documentation, reading, and note-taking. Content analysis is employed as the method of data analysis. The findings of this research reveal that the PTSP implementation consists of four stages: registration and login process, complaint submission process, follow-up on complaint status, and access to complaint status information. The PTSP implementation has proven to be effective and efficient due to the establishment of Standard Operations and Procedures for handling complaints. Community members can now submit complaints from anywhere and at any time, and they actively participate in improving public services. However, the lack of sufficient socialization has hindered the awareness and understanding of the PTSP application and its operational procedures.